IMPACTO DE ANTIMICROBIANOS NOS PARÂMETROS CINÉTICOS DE ESPERMATOZOIDES CRIOPRESERVADOS DE CATETOS - Matos, Tayná Moura; Moreira, Samara Sandy Jerônimo; Brazil, Andreza Vieira; Dantas, MaikoRoberto Tavares; Silva, Andréia Maria da; Souza-Junior, João Batista Freire; Silva, Alexandre Rodrigues (Ciência Animal, 2021)
The objective was to verify the impact of the addition of antimicrobials on the kinetic parameters of sperm in the cryopreserved semen of collared peccaries. Ejaculates from 10 adult male, obtained by electroejaculation, were used. The samples had their kinetic parameters evaluated by computer analysis (CASA). Subsequently, they were cryopreserved in Tris plus egg yolk (20%) and glycerol (3%), whether or not(control) added gentamicin (70μg/mL) or the combination penicillin (1000 IU/mL) and streptomycin (1mgE/mL) (P+E). After one week, the samples were thawed and evaluated similarly to fresh semen. In fresh semen, total motility of 95.3±0.8% and 72.1±3.5% progressive motility were observed. After thawing, there were no differences between treatments, except for the cross-beat frequency (BCF) parameter, which was negatively influenced by P+E, in relation to fresh semen (p<0.05). In conclusion, it is suggested the use of gentamicin as an antimicrobial for the cryopreservation of semen from peccaries.